O comércio de valor adicionado e a participação do Brasil nas cadeias globais de valor - Girotto, Cássia (2021)
The process of fragmentation of production in geographic space has been gaining strength since 1980, in recent decades international trade flows have come to make up a greater proportion of world trade and trade relations no longer occur only between developed countries, but also incorporate developing countries. In this new configuration of production, in which countries began to specialize in specific stages of production, the trade in intermediate goods increased significantly, so that the same product can cross several international borders to final consumption. In this sense, the available statistics on world trade tend to cause interpretive distortions, because the data are measured in terms of the gross value of exports, which can lead to double counting problems each time the product crosses a border. A solution to this problem is the measurement of exports in terms of domestic value added - VAD. In this scenario, this research aimed to analyze the evolution of Brazilian VAD trade, as well as Brazil's participation in Global Value Chains - GVCs, considering its main trading partners, through Trade in value-added indicators - TiVA and matrices Inputs Product of the 2018 release of the Inter-Country Input-Output Tables - ICIO made available by the Organization for Economic Co-operation and Development - OECD, which covers 64 countries and 36 sectors, for the years 2005, 2010 and 2015. it is noted that the products exported by Brazil to the European Union, China and South Korea are the ones with the highest percentage of VAD, in relation to total exports, since the products exported by Brazil in greater volume to these countries are primary, that is, , have little imported content in their composition. On the other hand, products exported by Brazil to Argentina, Mexico, and the Andean region are those with the lowest proportion of VAD in relation to the total value of exports, as they are high and medium technology products, which open up greater possibilities for incorporating content imported in production, contributing to the greater insertion of Brazil in the GVCs. In addition, the Brazilian participation in the GVCs, occurs in greater proportion as a provider of domestic value added (forward connection index) than as a demander of foreign value added (backward connection index), in accordance with the higher volume of exports of primary products, as there is less imported VAD in exports, which affects the Brazilian participation in GVCs as a demander of imported products. In this sense, an alternative for Brazil to generate more domestic added value and increase its participation in the GVCs would be to expand the internal processing capacity of some products, currently exported in natura, which would increase the space for the insertion of imported inputs, making the country more engaged in the GVCs, and in addition, it would generate more added value internally, which directly implies a greater volume of income for the worker and profit for the companies, contributing to raise the level of economic development.